HASIL BELAJAR EKONOMI MENGGUNAKAN TGT DAN TAI DENGAN MEMPERHATIKAN MINAT BELAJAR SISWA - Agus Komari; Pujiati Pujiati; Nurdin Nurdin (FKIP Unila, 2015)
This research is supported by learning outcomes economy which is low. The purpose of this research is to know the difference of economic learning outcomes and the presence or absence of interaction between students whose learning using TGT and TAI models regarding to the learning interest. Methods which is used is quasi experimentation. The population are 159 students with 53 students as the sample. Data collection is through interviews, observation, documentation, tests and poll. Hypotheses testing is using two sample independent test and variance two ways analysis. Based on analysis of data, it obtained that there are differences between learning outcomes economic and there is interaction between students whose learning are using TGT and TAI model regarding to the interest of learning.Penelitian ini dilatarbelakangi oleh hasil belajar ekonomi yang rendah. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan hasil belajar ekonomi dan ada tidaknya interaksi antara siswa yang pembelajarannya menggunakan model TGT dan TAI dengan memperhatikan minat belajar. Metode yang digunakan eksperimen semu. Populasi berjumlah 159 siswa dengan sampel 53 siswa. Pengumpulan data melalui wawancara, observasi, dokumentasi, tes dan angket. Uji hipotesis menggunakan t-test dua sampel independen dan analisis varians dua jalan. Berdasarkan analisis data diperoleh bahwa terdapat perbedaan antara hasil belajar ekonomi dan ada interaksi antara siswa yang pembelajarannya menggunakan model TGT dan TAI dengan memperhatikan minat belajar.Kata kunci: hasil belajar, minat belajar, TAI, TGT